Down and out: surviving the homelessness crisis - Lavelle, Daniel (Wildfire, 2023)
Daniel Lavelle left care at the age of nineteen, and experienced homelessness for the first time not long after. So began a life spent navigating social services that were not fit for purpose, leaving Daniel and many like him slipping through the cracks. In Down and Out, Daniel draws on his own experiences - as well as those of the witty, complex, hopeful individuals he has encountered who have been shunned or forgotten by the state that is supposed to provide for them - in order to shine a powerful light on this dire situation. Down and Out is a true state-of-the-nation examination of modern homelessness: assessing its significance, its precursors and causes, as well as the role played by government, austerity, charities, and other systems in perpetuating this crisis. Ultimately, it seeks to ask how we as a society might change our practices and attitudes so that, one day, we can bring this injustice to an end